Chronic carbon black nanoparticles exposure increases lung cancer risk by affecting the cell cycle via circulatory inflammation. (15th July 2022) - Zhang, Jianzhong; Li, Xin; Cheng, Wenting; Li, Yanting; Shi, Teng; Jiang, Yingying; Wang, Tao; Wang, Hongmei; Ren, Dunqiang; Zhang, Rong; Zheng, Yuxin; Tang, Jinglong
Abstract: As a widely used pure elemental carbon in colloidal particles, carbon black was listed as a group 2B carcinogen by IARC in 2010. The most available mechanism information about carbon black and carcinogenesis are from in vivo or in vitro studies. However, few studies concerned the nanoparticle's real-ambient exposure causing systemic change and further affecting the target organ. Herein, we used an ex vivo biosensor assay to investigate the transcriptome change of primary bronchial epithelial cells after treatment with the plasma from workers with long-term occupational carbon black exposure history. Based on ex vivo biosensor assay and transcriptome sequencing, we found the effect of internal systemic environment on epithelial cells after carbon black exposure was an inflammatory response, which mainly activates cell cycle-related pathways. After exposure to carbon black, the internal systemic environment could activate cancer-related pathways like epithelial-mesenchymal transition, hypoxia, TNF-α signaling via NF-κB. The hub genes in the carbon black group ( CDC20 and PLK1 ) and their correlation with the systemic environment were uncovered by constructing the protein-protein interaction network. Inflammatory cytokines, especially CRP, were strongly correlated with the expression of CDC20 and PLK1 . Besides, we also find a strong correlation between CDC20 and cytokinesis-block micronucleus endpoints in peripheral blood (rho = 0.591, P < 0.001). Our results show that long-term carbon black exposure might activate cell cycle-related pathways through circulating inflammation and increase the risk of cancer, while the oxidative stress caused by diesel exhaust particles are mainly related to PAHs exposure. After exposure to carbon black, the systemic environment could activate cancer-related pathways like diesel exhaust particles, increasing the risk of lung cancer. These attempts might provide a further understanding of the indirect effect of chronic occupational inhaled carbon black exposure on pulmonary carcinogenesis. Graphical abstract: Image 1 Highlights: Ex vivo biosensor assay was used to evaluate the lung cancer risk of carbon black exposure. Carbon black provoked systemic inflammation and activated cell cycle pathway in pulmonary. Carbon black affected the expression of PLK1 and CDC20 genes via circulatory inflammation. Carbon black exposure increased lung cancer risk different from the diesel exhaust particles.